2017
DOI: 10.1590/abd1806-4841.20175229
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the tendon sheath: a rare periungual location simulating myxoid cyst

Abstract: Giant cell tumor of the tendon sheath is a benign soft tissue tumor most frequent between the third and fifth decades of life. It can mimic and make differential diagnoses with several hand tumors. Definitive diagnosis and the treatment of choice are reached with complete resection and histopathological examination. Here we describe a case with clinical presentation similar to that of a myxoid cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In addition to differentiating cystic lesions from solid ones, ultrasound imaging can provide information about the tumour vascularity, size and its relation to the surrounding tissue 4 5. Plain radiography is not thought to be as important in making the diagnosis of GCTTS, but might detect the presence of cortical compression, intraosseous involvement or soft-tissue swelling 4. In this case, nodal osteoarthritis was also in the differential and was better elucidated by surgical excision and histopathological examination.…”
Section: Differential Diagnosismentioning
confidence: 89%
See 3 more Smart Citations
“…In addition to differentiating cystic lesions from solid ones, ultrasound imaging can provide information about the tumour vascularity, size and its relation to the surrounding tissue 4 5. Plain radiography is not thought to be as important in making the diagnosis of GCTTS, but might detect the presence of cortical compression, intraosseous involvement or soft-tissue swelling 4. In this case, nodal osteoarthritis was also in the differential and was better elucidated by surgical excision and histopathological examination.…”
Section: Differential Diagnosismentioning
confidence: 89%
“…These include lipoma, haemangioma, myxoid cyst, synovial sarcoma, aneurysmal bone cyst, fibroma and osteosarcoma 3 4. MRI is the most precise diagnostic imaging modality and reveals the GCTTS as low signal intensity on both T1-weighted and T2-weighted images, can accurately assess the tumour size and extent and help differentiate GCTTS from other solid soft-tissue tumours such as nerve-sheath tumours, haemangioma and soft-tissue sarcoma 4. However, sonography can be considered the first imaging modality in the work-up as GCTTS is typically a superficial lesion.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2] Some studies also reported GCTTS at knee, periungual, palmar and shoulder regions. [3][4][5][6] Cytological features are unique and are composed of two main components, including stromal cells and multinucleated giant cells. 2,7 First are the stromal cells or histiocyte-like cells that appear round to fusiform, eccentrically placed nuclei, even chromatin distribution, single micronucleoli and a small to moderate amount of cytoplasm with dispersed individual cells or loosely aggregated sheets.…”
Section: Plumworasawat S and Jinawath A Discussionmentioning
confidence: 99%